Does the administration of loop diuretics at the time of blood transfusion prevent transfusion‐associated circulatory overload (TACO)?. Issue 2 (February 2018) - Tafoya, Jesus; Dennington, Adrian J.; Haynes, Jamie
Abstract : EVIDENCE‐BASED ANSWER : The answer is unknown. In patients identified with TACO, 90% had received loop diuretics before, during, or after receiving blood components. However, mortality was higher in patients receiving diuretics before transfusion than during or after transfusion (SOR: B, longitudinal study with cohort analysis). In preterm infants, furosemide given before packed red blood cell (PRBC) transfusion decreases mean FiO2 compared with baseline (SOR: C, systematic review of RCTs with disease‐oriented evidence).